2022
DOI: 10.1088/1755-1315/1045/1/012138
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of increasing the yield of vetch-triticale grass mixture due to the use of a new complex biofertilizer

Abstract: In the Krasnodar Territory, on the experimental field of the Krasnodar Research Centre for Animal Husbandry and Veterinary Medicine, an experiment was conducted to determine the effect of a new complex biofertilizer on the yield and biometric indicators of a vetch-triticale fodder grass mixture. The conducted experiment shows that with the use of a new complex bio-fertilizer, an increase in the density of planting is observed in triticale (by 16 pieces or by 24%) and in Glinkovskaya vetch by (15 pieces or by 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The long-term effects of substituting organic materials for fine aggregates in concrete have been studied and offer various advantages. Research has shown that the application of organic materials in concrete can enhance its physical and thermal properties, leading to the improved long-term performance of the concrete [26,27]. Furthermore, the use of organic materials as a substitute for fine aggregates in concrete can contribute to sustainable concrete development.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effects of substituting organic materials for fine aggregates in concrete have been studied and offer various advantages. Research has shown that the application of organic materials in concrete can enhance its physical and thermal properties, leading to the improved long-term performance of the concrete [26,27]. Furthermore, the use of organic materials as a substitute for fine aggregates in concrete can contribute to sustainable concrete development.…”
Section: Introductionmentioning
confidence: 99%